Small Airway Dysfunction in Cough Variant Asthma: Prevalence, Clinical, and Pathophysiological Features - Yi, Fang; Jiang, Ziyu; Li, Hu; Guo, Chunxing; Lu, Hankun; Luo, Wei; Chen, Qiaoli; Lai, Kefang (Frontiers in Physiology, 2022)
Introduction: Small airway dysfunction (SAD) commonly presents in patients with classic asthma, which is associated with airway inflammation, disease severity and asthma control. However, the prevalence of SAD, its relationship with cough severity and airway inflammation, its development after antiasthmatic treatment in patients with cough variant asthma (CVA) need to be clarified. This study was aimed to investigate the prevalence of SAD and its relationship with clinical and pathophysiological characteristics in CVA patients, as well as the change in small airway function after antiasthmatic treatment. Methods: We retrospectively analyzed 120 corticosteroid-naïve CVA patients who had finished a standard questionnaire and relevant tests in specialist cough clinic including cough visual analog scale (VAS), differential cells in induced sputum, fractional exhaled nitric oxide (FeNO) measurement, spirometry and airway hyperresponsiveness. Information of one-year follow-up was recorded in a part of patients who received a complete cough relief after 2 months treatment. SAD was defined as any two parameters of MMEF% pred, FEF50% pred and FEF75% pred measuring less than 65%. Results: SAD occurred in 73 (60.8%) patients with CVA before treatment. The patients with SAD showed a significantly longer cough duration (24.0 vs 6.0, p=0.031) a higher proportion of female (78.1% vs 59.6%, p=0.029); older mean age (41.9 vs 35.4, p=0.005); and significantly lower FEV1% pred, FEV1/FVC, MMEF% pred, FEF50% pred, FEF75% pred, PEF% pred and PD20 (all p<0.01) as compared with patients without SAD. There were no significant differences in cough VAS, sputum eosinophils count, FeNO and TIgE level between patients with SAD and those without SAD. Among 105 patients who completed 2 months antiasthmatic treatment and repeatedly experienced spirometry measurement, 57 (54.3%) patients still had SAD, despite a significant improvement in cough VAS, sputum eosinophils, FeNO, FEF50% pred and PEF% pred (all p<0.01). As compared with the patients without SAD, patients with SAD showed no significant differences on the relapse rate (50.0% vs 41.9%, p=0.483) and wheeze development rate (10.4% vs 0%, p=0.063) during the follow-up. Conclusions: Small airway dysfunction occurred in over half of CVA patients, and persisted after short-term antiasthmatic treatment, which showed distinctive clinical and pathophysiological features.